Strategi Pengembangan Kewirausahaan Desa Melalui Rumah Produksi Jagung dalam Meningkatkan Perekonomian Masyarakat di Desa Kawengen - Nur Fatimah Apriliana; Muchammad Ronal Yuliyanto; Faizul A’la; Fadli Farhan Fikri; Ana febriyanti; Deewar Mahesa (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Kawengen Village, located in East Ungaran District, Semarang Regency, is one of the main corn-producing areas with strong potential to be developed into processed products with high economic value. However, limited community knowledge in product processing, business management, and marketing has prevented corn production from generating optimal added value. This community service program aims to strengthen village entrepreneurship through the establishment of a corn production house as a center for innovation, training, and business mentoring. The production house is expected to enhance community skills, promote economic independence, and support sustainable local economic development. The program was implemented through the PPK Ormawa initiative, which included socialization of corn-based product innovations, basic financial bookkeeping training, digital marketing training, product innovation workshops, and continuous mentoring in production, marketing, and financial management. The results demonstrate significant improvements in community skills in processing corn into value-added products, increased understanding of basic business financial management, and enhanced capacity to utilize digital media for market expansion. The corn production house also functions as a community collaboration hub that strengthens business development based on local resources. Overall, the strategy of developing village entrepreneurship through a corn production house has proven effective in encouraging the growth of productive community-based enterprises, strengthening local economic independence, and fostering entrepreneurial interest rooted in village potential.